Dynamic DM: prosperity through participatory good governance - Lal, Heera (New Delhi Prabhat Paperbacks, 2023)
As DM of Banda, Dr. Heera Lal's notable achievements and projects include - Startup Innovation Summit in Banda district, 90 plus awareness campaign to increase voting percentage, prison reform program, 'Save the pond' campaign in summer to deal with water crisis, eradication of malnutrition and Anna practice and to develop Kalinjar as a tourist destination. In addition to these, he has successfully implemented the plans, programs and priorities of the state government. These are a few special achievement and projects of Dr. Heera Lal as a DM of Banda. Not considering himself as an officer, but an ordinary servant of the society, he has displayed a wonderful and exemplary track record of his workmanship, foresight, teamwork and dedication as DM of Banda. If the DM and other administrative officers of every district discharge their responsibility with the same sense of duty, then there is no reason why every village, every district and the whole country will not be full of necessary facilities. Every Indian's life will be happy and India will write a new story of progress and advancement. 'Dynamic D.M.' is not only a motivational and readable book but it is also a powerful medium of social upliftment.
Keywords: Governance Sector; Public Administration; District Magistrate: Dr. Heera Lal IAS; Author as an IAS